The Relevance of Islamic Religious Values ​​in Fostering Religious Attitudes of Elementary School Students - Rohmah, Balqis Fauzatul (Tarsib: Jurnal Program Studi PGMI, 2025)
Relevance of Islamic religious values through elementary school religious culture to learners aims so that students are knowledgeable, can imagine and apply according to Islamic teachings, so that it becomes a good personality later, Islamic values that include aqidah, shari’ah and morals. Madrasah religious culture is the way or mindest of behaving all members of the elementary school based on the values of Islamic religious values. Elementary school religious culture plays a very important role, namely internalizing the value of Islamic religious values of learners in developingthe religious culture of elementary school. The formulation of the problems in this study is: 1). How is the concept of relevance of Islamic religious values in developing religious culture elementary school?; 2). What is the strategy of relevance Islamic religious values in developing religious culture elementary school?; 3). What are the supporting factors and inhibitions of the relevance of Islamic religious values in developing the religious culture elementary school2? This research uses a type of qualitative research with a field approach (field research) using descriptive methods. Data collection techniques using Interviews, Observations, Documentation. Data analysis techniques using data reduction, data presentation, verification. Checking the validity of findings with Credibility, Transferability, Forwardability, Confirmability. The concept of relenvance of Islamic values in elementary school can create an alternative solutions to the relevance of Islamic values, in the form of elementary school religious culture. Contrasting Islamic values (ta’aruf, tolerance, please help, tasamuh, tawazun, family nature) and discipline in the form of outlook on life, behavior, attitude through uswatun hasanah or tauladan in religious culture in accordance with the vision and mission of elementary school. Relevance of Islamic values through the container of madrasah religious culture with the policy of madrasah leadership as a supportive factor and other supporters such as: places of worship, vast elementary school courtyards, loudspeakers.